Abdominal aortic aneurysm: screening and management. Issue 1 (27th July 2018) - Giugliano, G.; Gerardi, D.; Annunziata, M.; Trimarco, B.; Esposito, G.; Stabile, E.
Abstract: Abdominal aortic aneurysm (AAA) is a frequent cause of death. Management of AAA includes different strategies: open surgery repair, endovascular repair and, for small AAA, medical therapy and careful follow‐up. Endovascular repair is a valid alternative to surgical repair, especially in patients whit high procedural risk. Abstract : Answer questions and earn CME: https://wileyhealthlearning.com/Activity2/6464194/Activity.aspx